Workplace barriers experienced by nurses in a tertiary level hospital during COVID-19 pandemic - Mina Akter,; M. Ali Reza Mondol,; Hafiza Sultana, (International Journal Of Community Medicine And Public Health, 2023)
Background: Nurses as frontline workers are experiencing barriers while discharging their duties. So, identifying workplace barriers experienced by nurses during COVID-19 is important because they are the most vital component of medical care. The present study aimed to identify the workplace barriers experienced by nurses in a tertiary-level hospital during the COVID-19 pandemic. Methods: This descriptive type of cross-sectional study was conducted among 200 nurses who were working in the non-COVID unit at Dhaka Medical College Hospital, Dhaka. Sampling was done by convenience sampling method. A semi-structured questionnaire was administered to the respondents to obtain information. Data were collected through a face-to-face interview. Results: The study found that 83% of respondents were females, and the mean age was 31.8±5.5. 52.5% completed a diploma in nursing, 61.5% of their working experience was 1-5 years, and 53% were working in the inpatient department. The major barriers identified were lack of guidelines, shortage of PPE, inadequate training coverage, lack of area for doffing and donning, and inadequate social distancing. Statistical analysis showed that different departments of work had a significant association (p<0.05) with inadequate training coverage. Conclusions: The barriers identified in this study should be overcome to improve nurses’ experiences in the workplace and in turn the quality of patient care during the COVID-19 pandemic.